Analisis Pendapatan Dan Strategi Bertahan Hidup Petani Karet Sebelum Dan Saat Pandemi Covid-19 Studi Kasus Di Desa Padang Manjoir Kecamatan Portibi Kabupaten Padang Lawas Utara - Siti Rahmah Ritonga, Muhammad Arif, Nurul Jannah (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
Rubber is a superior export commodity and is a source of foreign exchange for the country. This study aims to determine the differences in the income of rubber farmers and the survival strategies of rubber farmers before and during the COVID-19 pandemic in Padang Manjoir Village. The method used in this research is descriptive qualitative method, namely by field observations and interviews with informants at the location. The results showed that the income of rubber farmers before and during the COVID-19 pandemic was much different. The income of rubber farmers before Covid-19 was much greater than the income of rubber farmers during Covid-19. This is influenced by the price of rubber and the maintenance carried out by rubber farmers. Meanwhile, the strategies adopted by rubber farmers before and during Covid were not much different. Before Covid-19, rubber farmers continued to clear land, often tapped rubber and some of them had the capital to fertilize. Meanwhile, during the Covid-19 pandemic, more and more farmers were doing plantations around rubber fields and houses and then the produce was sold.